Lexico-semantic features of Kara-Nogais talk of the Mikhailovsk city, Stavropol Territory (by the linguistic expedition materials of NRU SSPI 2023) - Artyom S. Goncharov; Olesya S. Makarova; Inna I. Lizenko (Кавказология, 2023)
The article explores the models of vocabulary and semantics based on the example of folklore and speech creativity of the Kara-Nogais of Mikhailovsk (Stavropol Territory). Such sources on the language and culture of the Nogais as heroic epic, oral folk tradition and written documents are considered. The practical material of the article resulting in the expedition, which occurred in 2023. The information of the local periodical «Mikhailovskiye vesti» and the information agency «Cossack unity» is characterized. It’s revealed that the linguistic culture of the Kara-Nogais of the Stavropol Territory in modern times is unexplored, which causes interest in this sub-ethnos. The language features of the Kara-Nogais community of the residential complex «Admiral» in Mikhailovsk differ significantly from the Astrakhan and Circassian groups, which are more widespread in the North Caucasus Federal District. It is concluded that the linguistic synthesis of the Nogais and Karagash dialects led to the formation of a commonality of the Kara-Nogais dialect of the Nogais language with the vocabulary of the Kazakh and Karakalpak languages, and borrowings from Arabic, Persian and Russian languages caused a semantic shift, clearly seen in the example of a significant part of the cultural and social household concepts. It is concluded that morphologically, the Kara-Nogais dialect is agglutinative, parts of speech are divided into names, verbs and auxiliary parts of speech; the semantics of the dialect testifies to the extreme closeness of the society of the Kara-Nogais, who developed their own model of the world and the peculiarities of the hermeneutics of natural, social and cultural processes in the framework of life, speech creativity and performance of singing traditions, sayings, riddles.